Pengelolaan Persediaan Bahan Baku Mie Ayam Maryono Menggunakan POM-QM untuk Meningkatkan Operasional - Hidayat, Nurul; Tasa, Rizka Istianitati; Andriani, Saras; Triani, Selvy (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to enhance raw material inventory management at Mie Ayam Pak Maryono by utilizing POM-QM software, which is vital for Micro, Small, and Medium Enterprises (MSMEs) to boost operational efficiency and customer satisfaction. By employing Activity Based Costing (ABC) analysis, the study determines optimal order quantities and storage costs, revealing that POM-QM implementation reduces operational expenses and improves service quality. The ABC method effectively classifies inventory, with noodles and chicken making up 57,67 persen and 42,32 persen of total inventory costs, respectively. These findings highlight the significance of technology in inventory management, enabling MSMEs to monitor stock in real-time, minimize waste, and concentrate on product innovation and customer service, ultimately enhancing profitability and long-term sustainability.